2004
DOI: 10.1074/jbc.m410659200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Dependence of Group VIA Calcium-independent Phospholipase A2 Activity

Abstract: 2 activity, suggesting that regulation of this enzyme contributes to phospholipid accumulation. The levels of 80 kDa iPLA 2 protein do not change and thus cannot account for changes in enzyme activity. Reverse transcriptase and real-time PCR experiments show that splice variant iPLA 2 mRNAs are preferentially expressed during G 2 /M. Immunoblot analyses with an antibody directed against the N terminus of iPLA 2 revealed a ϳ50 kDa protein that is of appropriate size to be the truncated protein encoded by the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 47 publications
8
60
1
1
Order By: Relevance
“…Moreover, we showed that forced expression of ARD-iPLA 2 enhances p53 levels and G1-phase arrest in a concentration-dependent manner. Interestingly, the endogenous expression of an ankyrin-repeat domain of iPLA 2 has recently been described by another group of researchers, who postulate that this expression serves as a way to regulate iPLA 2 activity throughout the cell cycle (Manguikian and Barbour, 2004). It remains to be seen whether alternative splicing of iPLA 2 represents a way for the protein to be involved in cell-cycle control by interaction with p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we showed that forced expression of ARD-iPLA 2 enhances p53 levels and G1-phase arrest in a concentration-dependent manner. Interestingly, the endogenous expression of an ankyrin-repeat domain of iPLA 2 has recently been described by another group of researchers, who postulate that this expression serves as a way to regulate iPLA 2 activity throughout the cell cycle (Manguikian and Barbour, 2004). It remains to be seen whether alternative splicing of iPLA 2 represents a way for the protein to be involved in cell-cycle control by interaction with p53.…”
Section: Discussionmentioning
confidence: 99%
“…We next overexpressed the ARD-iPLA 2 -GFP [ankyrinrepeat domain of iPLA 2 fused to green fluorescent protein (GFP)], an alternatively spliced form of the iPLA 2 gene known to function as a negative regulator of iPLA 2 (Larsson et al, 1998;Manguikian and Barbour, 2004), in INS-1 cells. Transient expression suppressed cell proliferation in these cells, which was reversed when ARD-iPLA 2 -GFP expression decreased (Fig.…”
Section: G1mentioning
confidence: 99%
“…These two variants work similarly in our hands, because iPLA 2 -VIA-1 is the main form expressed in CHO cells, and transfection of iPLA 2 -VIA-2 has the same effect regarding TAG synthesis for the biogenesis of LD. Another two variants lack enzymatic activity but may act as dominant-negative inhibitors by precluding association of the active variants (41). It would be interesting to determine whether differential expression of active and inactive variants may account for LD generation during stress.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that, in addition to transcriptional control of iPLA 2 ␤ (Fig. 1A), its expression is regulated by proteolytic processing (48,49,59,60) or by alternative splicing (82,85). It has been reported that proteolytic cleavage of the N-terminal ankyrin repeats of iPLA 2 ␤ by caspase-3 or unknown proteases occurs in apoptotic cells (48,49) or even in nonapoptotic migrating cells (60) and agonist-treated islet ␤-cells (59), leading to activation of this enzyme.…”
Section: Discussionmentioning
confidence: 99%